Newtown urban school: re-coceptualising 21st century public education in the urban context. - Jali, Sibusiso (My University, 2014)
Urbanisation is a social phenomenon that is experienced in many cities all over the world. In Johannesburg, millions of people migrate into the city daily with hope for a better life, improved living conditions, work opportunities, sufficient public resources and facilities. The city is under pressure to provide adequate public resources to cope with the high influx of people moving into the city. As a result many resources and facilities, especially in the education sector, have experienced a decline in the quality of education and appropriate spaces for learning in the city. In trying to respond to the inclining population of the city, urban schools have been established in the Johannesburg. Urban schools are faced with many challenges such as: over-crowding, inadequate spaces for teaching and learning, lack of spaces for extracurricular activities and recreation, thus resulting in most learners performing poorly in their schooling careers. In most cases urban schools occupy old office buildings, which were not designed for the purpose of nurturing a young mind through education and recreation. These buildings serve as part of the problem with education and educating in the city. These buildings offer poor light quality, ventilation, and inadequate spaces critical for a well-functioning school and engaging with inquisitive young minds. The 21st century also presents a lot of opportunities and challenges for public education. The current South African public education system is still based on the early 19th century educational model, which was conceived and designed for the success of colonisation. Fix the next sentence about today... Though, the OBE system was recently introduced, but that has hasn’t had a great impact on the built environment of schools as it mainly continued using the old schools. Through re-conceptualising spatial environments that evoke the students’ engagement, enthusiasm and performance, the urban public school has the potential to make education more appealing and exciting to Johannesburg urban youth.
Keywords: Schools--Design and construction.